Comparing physician fee schedules in Canada and the United States - Katz, Steven J. (CENTERS for MEDICARE & MEDICAID SERVICES, 1992)
Although Canada and the United States have fundamentally different systems for financing health care, there are many similarities between the two countries in their approaches to physician payment. The similarities have increased recently with the adoption of the Medicare fee schedule. Canadian provinces have been using fee schedules for more than 20 years. This article provides an overview of the fee schedules used by Medicare and the four largest Canadian provinces, highlighting specific similarities and differences. We conclude that, although some differences in service definitions exist, the major areas of contrast relate to what services are paid for and how fees are updated. Updating fees is important because it affects how rapidly expenditures grow.